Oral flora of Python regius kept as pets. (24th January 2014) - Dipineto, L.; Russo, T.P.; Calabria, M.; De Rosa, L.; Capasso, M.; Menna, L.F.; Borrelli, L.; Fioretti, A.
Abstract This study was aimed at evaluating the oral bacterial flora of 60 Python regius kept as pets by culture and biochemical methods. All isolates were also submitted to antimicrobial susceptibility testing using the disc diffusion method. The oral cavity of snakes sampled harboured a wide range of Gram‐negative bacteria mainly constituted by Pseudomonas spp., Morganella morganii, Acinetobacter calcoaceticus, Aeromonas hydrophila, but also by Salmonella spp. Staphylococcus spp. was the commonest Gram‐positive isolates, and various anaerobic Clostridium species were also found. The most effective antimicrobial agents were enrofloxacin and ciprofloxacin, followed by doxycycline and gentamicin. Significance and Impact of the Study The oral cavity of snakes sampled harboured a wide range of bacteria. Our results suggest that people who come in contact with snakes could be at risk of infection and should follow proper hygiene practices when handling these reptiles.